2019
DOI: 10.1128/aac.02522-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Omadacycline against Rapidly Growing Mycobacteria

Abstract: The in vitro activity of omadacycline, a new tetracycline derivative, was evaluated against isolates of Mycobacterium abscessus, Mycobacterium chelonae, and Mycobacterium fortuitum using a broth microtiter dilution assay. Omadacycline had MIC90 values of 2 μg/ml, 0.25 μg/ml, and 0.5 μg/ml, respectively. The in vitro activity of omadacycline against rapidly growing mycobacteria indicates that it may have the potential to improve therapy for infections caused by these organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 4 publications
1
40
0
Order By: Relevance
“…Likewise, omadacycline and tigecycline had the same MIC 50 and MIC 90 against 28 drug-resistant clinical isolates (2 g/ml), while the MIC 50 and MIC 90 of eravacycline were 2-fold lower. Interestingly, while the present study was under review, a newly published study reported similar MICs for tigecycline and omadacycline against M. abscessus complex clinical isolates (19).…”
supporting
confidence: 50%
“…Likewise, omadacycline and tigecycline had the same MIC 50 and MIC 90 against 28 drug-resistant clinical isolates (2 g/ml), while the MIC 50 and MIC 90 of eravacycline were 2-fold lower. Interestingly, while the present study was under review, a newly published study reported similar MICs for tigecycline and omadacycline against M. abscessus complex clinical isolates (19).…”
supporting
confidence: 50%
“…A third published study tested omadacycline, tigecycline, and doxycycline against 24 M abscessus isolates [ 9 ]. The MIC 50 /MIC 90 of omadacycline and doxycycline were 1/2 mcg/mL and >64/>64 mcg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Omadacycline (PO/IV), Eravacycline (PO/IV) omadacycline [32,33] and eravacycline [34,35] have activity against reference and clinical strains N/A Report of one patient-noted clinical improvement [36] Tedizolid (PO/IV)…”
Section: N/amentioning
confidence: 99%
“…Eravacycline (a fluorocycline) is a new tetracycline analog approved for the parenteral treatment of complicated intraabdominal infections [34]. In vitro studies have shown both omadacycline and eravacycline to have similar antimicrobial activity to tigecycline against both reference and clinical M. abscessus strains [32,33,35]. Specifically as omadacycline is available as an oral formulation [58,59], it may have a role in treating chronic M. abscessus infections in outpatient settings.…”
Section: Novel Antimicrobialsmentioning
confidence: 99%